2009
DOI: 10.1158/1078-0432.ccr-09-1039
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat Inhibits Brain Metastatic Colonization in a Model of Triple-Negative Breast Cancer and Induces DNA Double-Strand Breaks

Abstract: Purpose: As chemotherapy and molecular therapy improve the systemic survival of breast cancer patients, the incidence of brain metastases increases. Few therapeutic strategies exist for the treatment of brain metastases because the blood-brain barrier severely limits drug access. We report the pharmacokinetic, efficacy, and mechanism of action studies for the histone deactylase inhibitor vorinostat (suberoylanilide hydroxamic acid) in a preclinical model of brain metastasis of triple-negative breast cancer. Ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 38 publications
8
107
0
1
Order By: Relevance
“…Concerning metastases, another study of an in vivo model of TNBC has reported that SAHA treatment is involved in the induction of DNA double-strand breaks suppressing brain metastatic colonization by 62% (54). Further studies that combine SAHA with DNA active drugs or radiation are needed in order to investigate thoroughly their actions against metastases.…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
“…Concerning metastases, another study of an in vivo model of TNBC has reported that SAHA treatment is involved in the induction of DNA double-strand breaks suppressing brain metastatic colonization by 62% (54). Further studies that combine SAHA with DNA active drugs or radiation are needed in order to investigate thoroughly their actions against metastases.…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
“…For example, as shown in Table 3, preclinical models from the Steeg and other laboratories suggest that a number of compounds (e.g., pazopanib and vorinostat, among others) can prevent brain metastases even if they are not efficacious in the "treatment" setting (i.e., drug dosing begun only after macrometastases are allowed to form, with tumor shrinkage as an endpoint; refs. 29,31,90,91). In a HER2 overexpressing model, Zhang and colleagues have recently demonstrated a profound prevention of experimental metastasis by the combination of lapatinib and the Src inhibitor saracatinib (32).…”
Section: Novel Designs and Clinical Settingsmentioning
confidence: 99%
“…Palmieri and colleagues have recently used this model to evaluate the novel histone deacetylase inhibitor vorinostat (11). This research suggests a new definition of targeted therapy: not only targeting a particular molecule, but also having the capability of targeting a specific metastatic site.…”
mentioning
confidence: 99%